The last song - Sparks, Nicholas (New York : Grand Central Publishing, 2009)
Her teenage life turned upside-down by her parents' divorce and her father's relocation out of state, Ronnie Miller remains bitter three years later when her mother urges her to spend a summer with her father.
Keywords: Teenage girls -- Fiction; Divorced parents -- Fiction